Understanding allied health practitioners' use of evidence-based assessments for children with cerebral palsy: a mixed methods study. Issue 1 (2nd January 2019) - O'Connor, Bridget; Kerr, Claire; Shields, Nora; Imms, Christine
Abstract: Purpose: Evidence-based assessments for children with cerebral palsy are not widely used by healthcare professionals in day-to-day practice. This study aimed to examine allied health practitioner experiences, perceptions, and use of assessments for children with cerebral palsy. Method: A mixed methods study was conducted in two rehabilitation organisations. Three focus group interviews explored therapists' assessment experiences with data analysed using interpretive description. Assessment practices of therapists ( n  = 55) were assessed through self-report questionnaire and case-file audit of children with cerebral palsy ( n  = 44). Results: Emergent themes described therapists' motivation to use evidence-based assessments on a behavioural continuum – I don't; I can't; I try; I do; We do; influenced by assessment satisfaction, child and family collaboration, organisational expectation, research fit, and time dedication. Only two of fifteen audited assessments were documented in more than 50% of files. Use was higher where assessments positively connected therapists, children and parents, and use was organisationally endorsed. The Cultural Cone for evidence-based assessment behaviour was conceptualised. Conclusions: "Engagement in" assessment appears to require a conceptual shift by therapists and organisations to understanding assessment as part of, not an adjunct to, therapy. The Cultural Cone framework may assist therapists and services in designing strategies to promote evidence-based assessment behaviours. Implications for rehabilitation: Therapists' can reflect on where they are positioned on the "use continuum" in the Cultural Cone framework, and consider the contextual influences contained in this framework to understand their motivation to use evidence-based assessments. Routine use of evidenced-based assessments for children with cerebral palsy by allied health practitioners remains generally low and therapists and service organisations need to consider ways to increase use. Where possible, therapists' should choose assessment tools that fully engage children and families and themselves in the assessment process. The Cultural Cone framework may be used to assist therapists and organisations identify and design site specific strategies to increase evidence-based assessment use in day-to-day practice.